2007
DOI: 10.1212/01.wnl.0000265220.64396.b4
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity within a large kindred with frontotemporal dementia

Abstract: The current results imply further genetic heterogeneity of frontotemporal dementia, as we detected only one GRN-linked family (about 1%). The value of discovering large kindred includes the possibility of a longitudinal study of GRN mutation carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
65
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 23 publications
4
65
0
Order By: Relevance
“…These higher frequencies can be explained by the presence of a strong founder effect of the Family DR8 founder mutation IVS115G4C in 8 out of 12 Belgian mutation carriers and the p.R493X mutation in 8 out of 39 U.S. mutation carriers, respectively . In addition, the number of studied patients was relatively low in some other studies [Huey et al, 2006;Bronner et al, 2007;Bruni et al, 2007]. Also, differences in patient recruitment methods, selection criteria, and geographical origin may account for the differences in mutation frequencies.…”
Section: Grn Mutation Spectrum Null Mutationsmentioning
confidence: 90%
See 4 more Smart Citations
“…These higher frequencies can be explained by the presence of a strong founder effect of the Family DR8 founder mutation IVS115G4C in 8 out of 12 Belgian mutation carriers and the p.R493X mutation in 8 out of 39 U.S. mutation carriers, respectively . In addition, the number of studied patients was relatively low in some other studies [Huey et al, 2006;Bronner et al, 2007;Bruni et al, 2007]. Also, differences in patient recruitment methods, selection criteria, and geographical origin may account for the differences in mutation frequencies.…”
Section: Grn Mutation Spectrum Null Mutationsmentioning
confidence: 90%
“…Subsequently, GRN mutations were also identified in most of the other described FTLDU-17 families (Table 1). Families Dutch-III, Brescia-F071, Biv, and Seattle B segregated a frameshift mutation resulting in a PTC [Benussi et al, 2008;Bronner et al, 2007;Leverenz et al, 2007;Bruni et al, 2007]. In Family HDDD2, the disease was caused by a missense mutation (p.A9D) introducing a charged amino acid in the signal peptide, resulting in the mislocalization of the protein [Mukherjee et al, 2006[Mukherjee et al, , 2008, which was shown to lead to a decrease in secreted GRN protein [Mukherjee et al, 2008].…”
Section: Grn Mutation Spectrum Null Mutationsmentioning
confidence: 99%
See 3 more Smart Citations